2012
DOI: 10.1080/0028825x.2012.661064
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene inhibits abscisic acid-induced stomatal closure inVicia fabavia reducing nitric oxide levels in guard cells

Abstract: The relationship between nitric oxide (NO) reduction and the inhibition of abscisic acid (ABA)-induced stomatal closure by ethylene was analysed. ABA treatment induced NO production and stomatal closure, but ethylene inhibited the effects of ABA on these two parameters. Like 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO), a specific scavenger of NO, haemoglobin (Hb), the potent scavenger of NO/carbon monoxide (CO) and N G -nitro-LArg-methyl ester (L-NAME), an inhibitor of animal nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
0
14
1
1
Order By: Relevance
“…Plant stomata closure is in association with the increasing of foliar abscisic acid (ABA) under flooding stress. However, the inhibitive effects of ethylene on ABA-induced stomatal closure were reported by Tanaka et al (2005) and She and Song (2012). In our study, lower ASA content tomato lines L0994 and ASVEG-6 showed increasing SC after flooding treatment, whereas higher ASA content tomato L6138 showed no increasing SC after flooding treatment.…”
Section: Resultscontrasting
confidence: 71%
“…Plant stomata closure is in association with the increasing of foliar abscisic acid (ABA) under flooding stress. However, the inhibitive effects of ethylene on ABA-induced stomatal closure were reported by Tanaka et al (2005) and She and Song (2012). In our study, lower ASA content tomato lines L0994 and ASVEG-6 showed increasing SC after flooding treatment, whereas higher ASA content tomato L6138 showed no increasing SC after flooding treatment.…”
Section: Resultscontrasting
confidence: 71%
“…Moreover, previous studies suggested that the decrease of leaf water content leads to the increase of ABA content to induce stomatal closure by regulating K + and anions channels (Jiang et al 2014, Kurepin et al 2015, Ha et al 2016, Brodribb and McAdam 2017. However, ethylene had a negative effect on stomatal closure induced by ABA (She and Song 2012, Chen et al 2013, Pedersen et al 2017, Najeeb et al 2018.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that, although ABA promotes ROS production in non-seed tissues, this hormone suppresses ROS production in imbibed seeds [74,75]. ABA treatment induced ⋅NO production in guard cells, mediated by nitrate reductase and a ⋅NO synthase-like enzyme [76,77,78,79]. Furthermore, ABA treatment caused sustainable increases of calcium ions (Ca 2+ ) in Commelina communis and Arabidopsis guard cells [80].…”
Section: The Chloroplast Is a Major Synthesis Site For Many Plant mentioning
confidence: 99%